PO046 Safety and tolerability of eslicarbazepine acetate as monotherapy in patients with newly diagnosed partial-onset seizures. (1st December 2017) - Trinka, E; Kowacs, P; Ben-Menachem, E; Elger, C; Moreira, J; Pinto, R; Ikedo, F; Pereira, A; Rocha, JF; Soares-da-Silva, P
Abstract : Purpose: To describe the safety of once-daily (QD) eslicarbazepine acetate (ESL) as assessed in a phase-III, randomised, double-blind, active-controlled, non-inferiority monotherapy study in adults with newly diagnosed partial-onset seizures (POS), in comparison with twice-daily (BID) controlled-release carbamazepine (CBZ-CR). Method: Patients (≥18 years) were randomised (1:1) to receive either ESL or CBZ-CR in a 3-step dose-level design. Each dose-level was then maintained through a 26 week Evaluation-Period (EP). Subjects who remained seizure-free at any dose-level continued through subsequent periods/phases. Safety assessments were carried out throughout the study. Results: The safety analysis set comprised of 813 patients (ESL, 401; CBZ-CR, 412). A similar percentage of subjects experienced at least 1 TEAE in the ESL group (75.3%) and CBZ-CR group (77.7%) and the majority of events were of mild intensity. The most frequently reported possibly-related TEAEs were (ESL; CBZ): headache (6.5%; 5.6%), dizziness (7.2%; 6.8%), nausea (4.5%; 6.8%), fatigue (4.7%; 4.4%), somnolence (5.2%; 7.0%) and increased gamma-glutamyltransferase (2.7%; 12.4%). Fewer subjects discontinued treatment due to a TEAE in the ESL group (13.5%) compared to the CBZ-CR group (18.0%). Conclusion: Once-daily ESL monotherapy demonstrated favourable safety in the study population. No new or unexpected safety findings emerged, compared with the adjunctive studies. Sponsored by BIAL-Portela and Cª S.A.